Bowings and fingerings technique in Baroque music / Zaleelah Borhan - Borhan, Zaleelah (Faculty of Music, 2008)
In violin playing we have to deal with distinct categorise of values. One of these can be called the absolute or unchangeble values and the other, the relatives or changable values. As the name implies, the first category is not affected by alteration of circumstances, wheareas the second category maybe modified or varied by the style of period, a change of locale, or the taste of the performer. The music Bach's for example, If we knew exactly how bach wanted in his music to sound, there still would remain the question or weather its should played precisely in the historical or weather the style should be adapted to fit modern ideas, means and surrounding. In my research the left hand is concerned with fingerings which fingering in playing double stop and also in shifting and also problems when playing a chords and thrills which generally cause most of the trouble for the violinist.